Effect of integrated nutrient management through vermicompost and inorganic fertilizers on growth, yield, nutrient uptake and oil quality of geranium (Pelargonium graveolens L’ Her. ex Ait.) grown on alfisol - Singh, Munnu (Journal of Spices and Aromatic Crops, 2011)
The effect of vermicompost and inorganic fertilizers (NPK) on growth, herbage, essential oil yield, oil quality and nutrient uptake pattern of geranium (Pelargonium graveolens) was studied at Bengaluru in a semi-arid climate. Among the five treatments compared, the combination of vermicompost @ 5 t ha-1 + 50% recommended NPK fertilizer (100 : 25 : 25 kg ha-1) gave significantly better growth, high fresh herbage yield and oil yield which was on par with full dose of fertilizer NPK (200 : 50 : 50 kg ha-1). A similar pattern was noticed in case of nitrogen, phosphorus and potassium uptake by plants. Oil content and oil quality were not influenced by vermicompost and inorganic fertilizers, alone or in combination.